2022
DOI: 10.3390/agriculture12111864
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Heavy Metals Contamination in Soil and Two Rice (Oryza sativa L.) Varieties Irrigated with Paper Mill Effluent

Abstract: Heavy metal pollution from industrial wastewaters has become an issue of global concern. These wastewaters are frequently used for inland irrigation which possess a serious risk of heavy metal contamination of both soil and cultivated crops. The problem is more common in developing countries like India where industrial wastewaters are often discharged without appropriate treatments. Therefore, this study aimed at assessing the impact of paper mill effluent for irrigation on the growth, productivity, and heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In a report, Laohaprapanon et al [30] stated that wood industry-based waters have high total organic carbon (1376 ± 62 mg/L) and COD (4380 ± 94 mg/L) levels of extreme environmental toxicity even if heavily diluted. Similarly, the study on rice fields irrigated with paper mill wastewater in the Saharanpur district revealed the serious pollution of such waters [4]. Zones 1 and 3 showed a strong positive correlation with increased TSS in pond water (Figure 2a) matching in the same PCA quadrant.…”
Section: Status Of Water Quality and Heavy Metals Pollution In Pond W...mentioning
confidence: 72%
See 3 more Smart Citations
“…In a report, Laohaprapanon et al [30] stated that wood industry-based waters have high total organic carbon (1376 ± 62 mg/L) and COD (4380 ± 94 mg/L) levels of extreme environmental toxicity even if heavily diluted. Similarly, the study on rice fields irrigated with paper mill wastewater in the Saharanpur district revealed the serious pollution of such waters [4]. Zones 1 and 3 showed a strong positive correlation with increased TSS in pond water (Figure 2a) matching in the same PCA quadrant.…”
Section: Status Of Water Quality and Heavy Metals Pollution In Pond W...mentioning
confidence: 72%
“…The findings showed a significant accumulation of potentially toxic elements in rice fields, with only health risks in the PR-121 rice variety, which indicates a minor accumulation in the edible part of the crop [4]. Heavy metals bioaccumulation in human-consumed crops can lead to health risks varying from diarrhea to anemia, mental and central nervous dysfunction, childbirth complications, and cancer [4]. Thus, adequate monitoring of water resources either for direct consumption or to be used for agricultural production is crucial to avoid contracting transmissible diseases such as cholera and typhoid [5,6].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Heavy metal concentration increased in TWW treated soils. Many authors evidenced that the increased heavy metals in soils were associated with reduced microbial populations, their diversity and activity; cytotoxic effect on soils; and phytotoxicity in plants leading to reduced plant growth and chlorosis (AL-Huqail et al, 2022). The hazard of heavy metals can be contrasted by the gain of OM content in soil which consequently, allowing a major detention from soils, decreases the danger that toxic elements can reach deep layers or superficial groundwater (Khaskhoussy et al, 2022).…”
Section: Gas Exchangementioning
confidence: 99%